CHANGES IN VO2MÁX AND BODY COMPOSITION DURING PUBERTY (Fiep Bulletin - online, 2015)
the changes in VO2máx and body composition during puberty it is not well elucidated.  Objective: to analyze the changes in VO2máx and body composition during the puberty in male subjects. Methods: the data consisted of 87 subject, from 7 to 19 years old, classified by the sexual maturation stages proposed by Tanner (1962): stage 1 (n=35), stage 2 (n=23), stage 3 (n=11), stage 4 (n=12) e stage 5 (n=08). Initially were measured height and weight (W). To estimate the percentage of fat (%F) the Slaughter (1988) equation was used. The fat mass (FM) and the fat free mass (FFM) were calculated: FM= W (%F/100) and FFM= W-FM. To determinate the VO2máx was used the 20m shuttle-run test propose by Léger (1988).  Analyzes of variance (one-way) and the post-hoc of Tukey were used to test possible differences between the groups, with p
Keywords: VO2máx; body composition and puberty.